Private Equity Exits in FInland - Auramo, Oskari (My University, 2019)
Private equity has become a significant force in the global financial markets. The industry has been booming as record-high global fundraising figures have been reported in the past years. Private equity refers to a form of investing in unlisted securities. The returns are realized when the asset is divested in what is known as the exit. The purpose of this thesis is to study the determinants of the exit channel decision in the Finnish market. A quantitative approach has been chosen to answer the research question. A multinomial logistic regression with Firth’s penalized maximum likelihood estimation has been applied to a data set of Finnish private equity exit transactions. This thesis presents a unique hand-compiled data set consisting of 101 transactions between 2012 and 2018. The data set has been constructed by combining various sources. The results provide strong support for target company-related characteristics explaining the exit channel decision. According to the models, smaller and less profitable companies are more likely to be sold to strategic buyers. In addition, the results support the existence of an IPO size hurdle. The results also provide weak support for market and fund structure factors as determinants of the exit vehicle. Stock market valuation levels and returns as well as the investment holding period are found affect the exit behaviour. The results supplement previous private equity exit channel research by providing detailed information of the Finnish market.
Keywords: private equity,mergers and acquisitions,IPO